Alih Inovasi Teknologi Dalam Peningkatan Profit Kedelai - Imam Sutrisno (UM Purwokerto Press, 2021)
The ability to increase national soybean productivity is still low. Every year the obstacle that causes farmers is it is difficult to procure quality soybean seeds and access certified seed stocks in captivity. In this condition, there needs to be a solution to support the use of quality seeds and the ease of purchasing superior/quality seeds by farmers independently and sustainably. The results of this study stated that 1) Detap 1 variety was in accordance with preferences and significantly increased soybean farming income in supporting the availability of quality consumption soybeans in East Java; 2) Gapoktan independence in preserving the Detap 1 variety with local seed farming; 3) Regional assistance by agricultural ministers and agricultural extension workers consistently as facilitators and regulators of leading technological innovations.